(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Measles remains a significant public health issue, particularly in countries with low vaccination coverage. In recent years, an increase in measles cases has been observed, including among adults, due to vaccine hesitancy and lack of immunity.